The Hypothetical Household Tool (HHoT) in EUROMOD: a new instrument for comparative research on tax-benefit policies in Europe - Tine Hufkens; Tim Goedemé; Katrin Gasior; Chrysa Leventi; Kostas Manios; Olga Rastrigina; Pasquale Recchia; Holly Sutherland; Natascha Van Mechelen; Gerlinde Verbist (European Commission, Joint Research Centre (JRC), 2019)
This paper introduces the Hypothetical Household Tool (HHoT), a new extension of EUROMOD, the tax-benefit microsimulation model for the European Union. With HHoT, users can easily create their own hypothetical data, which enables them to better understand how policies work for households with specific characteristics. The tool creates unique possibilities for an enhanced analysis of taxes and social benefits in Europe by integrating results from microsimulations and hypothetical household simulations in a single modelling framework. Furthermore, the flexibility of HHoT facilitates an advanced use of hypothetical household simulations to create new comparative policy indicators in the context of multi-country and longitudinal analyses. In this paper, we highlight the main features of HHoT, its strengths and limitations, and illustrate how it can be used for comparative policy purposes.
Keywords: 330; HHoT; microsimulation model; hypothetical household simulations; European Union